Educational resource for antimicrobial resistance and stewardship for dentistry programmes: a research protocol - Ang, Chuan Yok; Dhaliwal, Jagjit Singh; Muharram, Siti Hanna; Akkawi, Muhammad Eid; Hussain, Zahid; Rahman, Hanif; Kok, Yuh Yen; Dhaliwal, Sachinjeet Kaur Sodhi; Ming, Long Chiau (BMJ Publishing Group, 2021)
Introduction: Antimicrobial resistance (AMR) is a global public and patient safety issue. With the high AMR risk, ensuring that the next generation of dentists that have optimal knowledge and confidence in the area of AMR is crucial. A systematic approach is vital to design an AMR content that is comprehensive and clinically relevant. The primary objective of this research study will be to implement a consensus-based approach to elucidate AMR content and curriculum priorities for professional dentistry programmes. This research aims to establish consensus along with eliciting opinion on appropriate AMR topics to be covered in the Bachelor of Dental Surgery syllabus.